Phenotypic and Molecular Characterization of K54-ST29 Hypervirulent Klebsiella pneumoniae Causing Multi-System Infection in a Patient With Diabetes - Shao, Chunhong; Xin, Li; Mi, Peiyan; Jiang, Meijie; Wu, Haiyan (Frontiers in Microbiology, 2022)
Worldwide, hypervirulent Klebsiella pneumoniae (hvKp) is one of the leading causes of multisystem infection. Serotype K54 has also been considered as one of the hvKp-associated capsular types that are rarely reported. In this study, we reported a K54-ST29 hvKp isolated from a 58-year-old male patient with diabetes in a teaching hospital in China. The patient rapidly developed sepsis and brain abscess, with a lethal multiple-organ-system failure due to K54 hvKp infection. This K54 hvKp isolate showed high level of toxicity in a mouse infection model and was susceptible to all the tested antibiotics. The isolate was fully sequenced, and its genome was compared with the available K54 K. pneumoniae genome. We predicted 133 virulence and pathogen-related genes, including those involved in fimbriae synthesis, iron transport, and enterobactin synthesis. Sequence alignment revealed >90% similarity among seven K54 K. pneumoniae strains. Our data suggest that community-acquired infection caused by hypervirulent K54 K. pneumoniae in patients with diabetes is a concern in East Asia.